2019
DOI: 10.3389/fneur.2019.01267
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic Outcomes of Direct and Combined Bypass Surgery in Moyamoya Disease

Abstract: Objective: To identify associated risk factors for the angiographic outcomes after direct and combined bypass surgery in moyamoya disease (MMD).Methods: All direct and combined bypass procedures performed from June 2009 to May 2015 were screened in this prospective cohort study. Patients who acquired presurgical and follow-up catheter angiography were included. Bypass patency and postoperative collateral formation were evaluated. Univariate and multivariate logistic regression analyses were performed to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 32 publications
(51 reference statements)
0
29
1
Order By: Relevance
“…Overall definite bypass patency after 6 to 12 months was excellent with 98.1% and, therefore, slightly higher than reported in the literature (3,4). One bypass which was confirmed to be occluded in the follow-up DSA was already displayed as non-patent in the post-operative CTA.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Overall definite bypass patency after 6 to 12 months was excellent with 98.1% and, therefore, slightly higher than reported in the literature (3,4). One bypass which was confirmed to be occluded in the follow-up DSA was already displayed as non-patent in the post-operative CTA.…”
Section: Discussionmentioning
confidence: 52%
“…Surgical revascularization with direct extracranial-intracranial (EC-IC) bypass is the most common therapy in adult moyamoya patients (1,2). Long-term bypass patency has been shown to be between 88 and 97% in these patients (3)(4)(5)(6). The risk of bypass occlusion appears highest during the first week after surgery and declines over time as the bypass matures (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct revascularization is currently recognized as the superior treatment paradigm for adult hemorrhagic MMD to reduce the incidence of rebleeding [ 9 , 10 , 20 ]. However, hemorrhagic MMD was indicated to be more prone to delayed anastomotic occlusion compared with ischemic MMD, with a long-term graft patency rate of 54.9–77.5% [ 12 , 13 ]. Such a high rate of anastomotic occlusion prompted us to conduct in-depth research on the mechanism of delayed anastomotic occlusion and its impact on the long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, direct or combined revascularization has been recognized as the most effective treatment strategy to reduce the risk of future intracranial hemorrhages in hemorrhagic MMD [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. However, Zhao et al and Ge et al, from our institution, demonstrated that hemorrhagic presentation predicts lower patency rates (54.9–77.5%) and unsatisfactory neoangiogenesis after direct/combined bypass [ 12 , 13 ]. Such a high rate of delayed anastomotic occlusion prompted us to conduct an in-depth analysis of this phenomenon.…”
Section: Introductionmentioning
confidence: 99%